Hepatic Hemangioma in Celiac Patients: Data from a Large Consecutive Series. (12th January 2015) - Massironi, Sara; Branchi, Federica; Rossi, Roberta Elisa; Fraquelli, Mirella; Elli, Luca; Bardella, Maria Teresa; Cavalcoli, Federica; Conte, Dario
Abstract : Background and Aims . Hepatic hemangioma (HH) has a widely ranging prevalence. The etiology is unclear; however, associations with autoimmune disorders have been described. We aimed at evaluating the prevalence of HH in celiac disease. Methods . Ninety-seven consecutive patients with celiac disease (18 M, 79 F, median age 41, and range 17–84 years) underwent liver ultrasound between January 2011 and 2012. The findings were compared with those of 1352 nonceliac patients (581 M, 771 F, median age 50, and range 16–94 years), without liver disease or previously detected HH, who underwent US in the same period. Results . Ultrasonographic findings consistent with HH were observed in 14 celiac patients (14.4%), a prevalence significantly higher than in controls (69 cases, 5.1%) (P = 0.0006 ). Subgroup analysis showed that, among women, the prevalence of HH was 16.4% in the celiac disease group (13/79) compared with 5.9% in controls (46/771) (P = 0.002 ). In celiac setting, HH had a median diameter of 1.3 cm and presented as a single lesion in 12 cases (86%). Conclusions . Our findings are consistent with a significantly higher prevalence of HH in celiac patients. Although mechanisms underlying this association remain unclear, autoimmune and metabolic processes, as well as alterations of gut-liver axis equilibrium, could play a role.